2018
DOI: 10.1590/s1806-37562018000000049
|View full text |Cite
|
Sign up to set email alerts
|

Six-minute walk distance and survival time in patients with idiopathic pulmonary fibrosis in Brazil

Abstract: Objective:To determine the cut-off point for the six-minute walk distance (6MWD) that indicates lower survival time in patients with idiopathic pulmonary fibrosis (IPF) in Brazil. Methods:This was retrospective study carried out in two referral centers for IPF. The 6MWT was performed twice, considering the highest value of the 6MWD. Various cut-off points were estimated, in absolute values and in percentage of predicted values, using ROC curves, the Kaplan-Meier method, and data from other studies. Results:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
1
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
0
18
1
1
Order By: Relevance
“…It appears that such an association also applies to respiratory diseases such as COPD and IPF. However, the difference between the values found by Mancuso et al 10 and those found by other authors might be due to the study design and the analyses performed in the study. Because it is impossible to compare the study conducted by Mancuso et al 10 with all previous studies, I will compare it with the study involving the highest number of patients and based on data from the study by du Bois et al 7 …”
contrasting
confidence: 63%
See 3 more Smart Citations
“…It appears that such an association also applies to respiratory diseases such as COPD and IPF. However, the difference between the values found by Mancuso et al 10 and those found by other authors might be due to the study design and the analyses performed in the study. Because it is impossible to compare the study conducted by Mancuso et al 10 with all previous studies, I will compare it with the study involving the highest number of patients and based on data from the study by du Bois et al 7 …”
contrasting
confidence: 63%
“…The first question is why the indicator of poor prognosis found in a study conducted in Brazil 10 is significantly different from those found in studies conducted elsewhere. 7 , 11 - 13 According to Mancuso et al, 10 this might be due to differences in reference values for the 6MWT across countries. 14 There is evidence that the 6MWD is longer in individuals living in Latin America than in those living in Europe or the USA.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…[8][9][10][11] 6MWT is a commonly used surrogate test to predict outcomes in patients with IPF. In 6MWT, the distance walked in 6 min, [22] decrease in the distance walked at 24 weeks, [13] recovery of heart rate after 1 min of the test, [23] and oxygen desaturation [24] are associated with increased mortality in patients with IPF. Gender, age, and the two physiologic variables in PFT "FVC" and "DLCO" have been recently integrated into the gender, age and pulmonary physiology (GAP) index, [25] which can also precisely predict the survival rate in patients with IPF.…”
Section: Introductionmentioning
confidence: 99%